Assessing the accessibility of care facilities for older adults with integration of their choice preferences: a case study of Fuzhou’s main urban area, China - Zhang, Qiuyi; Wu, Siying; Lin, Gang; Yan, Xiaofen (Frontiers in Public Health, 2025)
Against the backdrop of rapid population aging in China, optimizing the spatial allocation of older adults’ care facilities has become increasingly important. This study evaluates both objective and preference-based accessibility to address gaps in precision planning for aged care. Focusing on Fuzhou’s main urban area, this research investigates three facility types: institutional care service facilities, community day care centers, and home-based care service stations. Using a modified Gaussian two-step floating catchment area (MG2SFCA) method with residential communities as analytical units, this research conduct accessibility analysis integrated with older adults’ choice preferences to quantify disparities between actual and willingness-weighted accessibility. Findings reveal significant spatial mismatches between facility distribution and older adults’ needs across all three types. Building on this, we develop street-level typological classifications (Gain/Attenuation/Risk) to propose context-specific optimization strategies. The study’s innovations lie in: (1) advancing analytical precision through micro-scale community units, and (2) incorporating subjective care preferences into spatial evaluation models, thereby providing evidence-based planning references for age-friendly city development.